Effects of acupuncture-related treatments on blood lipid levels in patients with coronary heart disease: A comprehensive review and network meta-analysis - Yuting Cui; Ziyun Li; Ping Gao; Weiming Xu; Jingqing Hu (Complementary Therapies in Medicine)
Background: Dyslipidemia is considered a substantial risk factor for coronary heart disease (CHD). Blood lipid levels in patients with CHD influence cardiovascular events. Therefore, it is critical to monitor and control these levels. As a traditional, complementary alternative therapy, acupuncture regulates blood lipid levels in patients with CHD. More acupuncture-related treatments are currently available. However, systematic reviews or evidence-based summaries have yet to be conducted. Methods: This study included a randomized controlled trial of the effects of acupuncture-related therapies on blood lipid levels in CHD patients. The outcome indicators were changes in the TC, TG, LDL-C, and HDL-C levels. Two independent reviewers extracted data from PubMed, Web of Science, EMBASE, Cochrane Library, Medline (Ovid), China Knowledge Network, Wanfang, Vipshop, and SinoMed databases until January 7 2024. The literature quality was assessed using RevMan 5.4.1. The data were analyzed using the Frequentist network meta-analysis with STATA 15.1 software. Network meta-analysis was used to compare direct and indirect evidence, and a cumulative ranking curve (SUCRA) was used to evaluate the curative effect. For consistency, global inconsistency and ring-inconsistency test evaluations were used. The Cochrane bias risk assessment tool was used to assess quality. Results: Fourteen studies with 1416 patients were included in the study. The evidence network shows that there are many studies on acupuncture and warm acupuncture. According to the direct comparison and SUCRA ranking, acupuncture reduced TC [− 1.82 (− 3.36, − 0.28)], heat-sensitized moxibustion lowered TG [− 2.12 (− 3.55, − 0.69)], LDL-C [− 1.37 (− 2.09, − 0.66)], and increased HDL-C [0.87 (0.52, 1.22)]. These two interventions were the first in the SUCRA ranking. The inconsistency analysis revealed that direct evidence corresponded with indirect evidence. There were some methodological defects in the included studies, and some studies did not implement blinding methods, had small sample sizes or other problems. Conclusions: Heat-sensitized moxibustion significantly lowered TG and LDL-C levels and elevated HDL-C levels. Acupuncture significantly reduced TC levels. Heat-sensitized moxibustion is a more effective intervention than other acupuncture-related treatments for regulating blood lipid levels in patients with CHD. However, this study has several limitations, and clinical practice should be performed as needed.